Testing the Validity of Patellar Measurements in Sex Estimation – A Computed Tomography Study in a Contemporary Polish Population - Jakubik, Karol; Jeżak, Mikołaj; Nowińska, Aleksandra; Grudzień, Monika; Piech, Piotr; Karpińska, Justyna; Staśkiewicz, Grzegorz (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Human skeleton-based sex estimation is a major topic of interest for forensic anthropologists. Various bones have been examined for sex heterogeneity. The most commonly used include skull and pelvis, however they may not always be used due to damage or fragmentation. The patella has been shown to be resistant to postmortem changes, which creates a potential use for determining the sex of unknown human remains. Materials and methods: The samples were gathered from patients examined by computed tomography angiography (CTA) of lower extremities in University Hospital No. 4 in Lublin. Exclusion criteria included patellar fractures, knee replacement and advanced osteoporosis. A total of 120 CTA examinations of 65 males and 55 females, were included in the analysis. Four measurements for every patella: craniocaudal patella dimension (CCP), transverse dimension (TP), anteroposterior dimension (APP) and patellar angle (PA), were obtained from CTA images. Results: The statistical analysis proved that sex differences of all variables, except for PA, were statistically significant (p < 0,001). Conclusions: Patellar measurements can be helpful in sex determination in the Polish population. CT is a useful tool for skeleton-based sex identification.